Ukraine’s Population Compared to European Post-Communist Countries in 1990 and 2020 - Yevhen Matviyishyn (Journal of Geography, Politics and Society, 2022)
The aim of the study is to present the changes in the population and its demographic structure in Ukraine compared to other European post-communist countries. Classic demographic indicators were applied. In comparison to other analyzed countries, Ukraine has an average pace of population decline, a low aging rate and a persistently clear advantage of the number of women over men. This is the result of all three factors: loss of part of the territory with the population inhabiting it, natural decrease and negative migration balance.